PENGARUH PEMBERIAN EKSTRAK KULIT PISANG KEPOK (Musa acuminata) TERHADAP PENURUNAN KADAR MALONDIALDEHID (MDA) PARU MENCIT JANTAN (Mus musculus) YANG DIPAPAR ASAP ROKOK - Dewi, Sapna Kurnia; Lokapirnasari, Widya Paramitha; Meles, Dewa Ketut; Mustofa, Imam; Mafruchati, Maslichah; Hamid, Iwan Sahrial (Journal of Basic Medical Veterinary, 2019)
This research aimed to determine the effect of kepok banana peel extract (Musa acuminata) given by per oral in decreasing levels of malondialdehyde (MDA) in lung of male mice (Mus musculus) which was exposed to cigarette smoke. The 24 experimental male mice were divided into 6 groups. The therapy was given for 14 days, all mice were sacrificed and lung MDA level were examined with thiobarbituricacid (TBA) methods. The result of the data analysis test using one-way ANOVA (Analysis of Variance) showed that there were significant differences between the group of animals that exposed to cigarette smoke ( = 840.50± 186.47 nmol / g) and the group of animals that were given with extract of kepok banana peel 56 mg / kg bw  ( = 6471.25 ± 69.25 nmol/g). Besides that, there was an significant difference between the groups of animals that were exposed cigarette smoke ( = 840.50± 186.47 nmol / g) with the group of animals that were given with vitamin C 260 mg/kg bw ( = 555.25± 61.16 nmol / g). It could be concluded that extract of kepok banana peel and vitamin C could decrease MDA levels in lung of male mice which was exposed cigarette smoke. The increased therapy dose gave affect in lowering levels of malondialdehyde in lung.